Construction of NiPx/MoS2/NiS/CdS composite to promote photocatalytic H2 production from glucose solution. Issue 10 (8th June 2021) - Zheng, Xiuzhen; Wang, Xulin; Liu, Jiafang; Fu, Xianliang; Yang, Yang; Han, Huijuan; Fan, You; Zhang, Sujuan; Meng, Sugang; Chen, Shifu
Abstract: Constructing multi‐component photocatalyst is an efficient method to achieve high photocatalytic efficiency. In this work, CdS nanorods modified with NiS nanoparticles are first prepared to improve the photocatalytic performance, as no H2 generates on single NiS or CdS catalyst from glucose solution. MoS2 and NiPx, as the cocatalysts for H2 production, are loaded on the surface of NiS/CdS composite. With step‐by‐step solvothermal synthesis, four components (CdS, NiS, Mo2 S, and NiPx ) are fully combined in the NiPx /MoS2 /NiS/CdS nanorods, generating many intimate contact interfaces. Moreover the optimized NiPx /MoS2 /NiS/CdS performs a significantly increased photocatalytic activity, with H2 production rate at 297 µmol h –1 g –1 . The synergistic effects of heterostructure (NiS/CdS) and cocatalysts (MoS2 and NiPx ) are the main reasons in enhancing photocatalytic performance, which facilitate the separation of charge carriers and prolong their lifetimes. This work provides an effective strategy to design photocatalysts with multiple components and fast charge separation for highly efficient H2 production. Abstract : Constructing multi‐component photocatalyst is an efficient method to achieve high photocatalytic efficiency. For NiPx /MoS2 /NiS/CdS composite, the synergistic effects of heterostructure (NiS/CdS) and cocatalysts (MoS2 and NiPx ) are the main reasons in enhancing photocatalytic performance, which facilitate the separation of charge carriers and prolong their lifetimes.